2015
DOI: 10.1080/23302674.2015.1050079
|View full text |Cite
|
Sign up to set email alerts
|

A game theoretic model for coordination of single manufacturer and multiple suppliers with quality variations under uncertain demands

Abstract: In this paper, a game theoretic model for supply chain coordination problem is studied. The supply chain coordination problem involves one manufacturer and multi-suppliers with quality variations under demand uncertainty. The number of defective parts purchased from suppliers is unknown to the manufacturer while each supplier can determine the standard deviation of defective items. The relationship between the manufacturer and the suppliers is modelled by a non-cooperative game. The non-cooperative game model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Liu et al [33] considered both the production competition between partially substitutable products made by different manufacturers, and the competition between retail stores, and they found that as consumers' environmental awareness increases, retailers and manufacturers with superior ecofriendly operations will benefit [33][34][35][36]. Ghosh and Shah [37] studied supply chain coordination issues arising out of green supply chain initiatives and explored the impact of cost sharing contract on the key decisions of supply chain players undertaking green initiatives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu et al [33] considered both the production competition between partially substitutable products made by different manufacturers, and the competition between retail stores, and they found that as consumers' environmental awareness increases, retailers and manufacturers with superior ecofriendly operations will benefit [33][34][35][36]. Ghosh and Shah [37] studied supply chain coordination issues arising out of green supply chain initiatives and explored the impact of cost sharing contract on the key decisions of supply chain players undertaking green initiatives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Channel design is one of the important research streams in closed-loop supply chains [6]. Stackelberg competition models are widely used to describe the relationship between manufacturers and retailers [7][8][9][10][11][12][13][14][15][16]. Savaskan et al (2004) [7] studied the problem of choosing the appropriate closed-loop supply chain structure for collecting the used products.…”
Section: Closed-loop Supply Chain Design Problemmentioning
confidence: 99%
“…Stackelberg game is closely related to bi-level programming which is a hierarchical optimization problem including upper and lower level to find good strategies for optimizing their objective function values. 31,32 Adapting to the problem in this article, a multi-objective bi-level programming model is proposed to tackle the Stackelberg game.…”
Section: Stackelberg Game Modelmentioning
confidence: 99%